A case report of young-onset type 2 diabetes patient with severe metabolic dysregulation carrying an LRP6 variant - Dan Xiang; Li Yuan; Shuaiju Liao; Yangtian Wang (Frontiers in Endocrinology, 2026)
Background The global epidemic of type 2 diabetes mellitus (T2D), along with its rising prevalence among younger populations, raises substantial public health concerns; severe hypertriglyceridemia (sHTG) is a major risk factor for acute pancreatitis. Insulin resistance in T2D often coincides with dyslipidemia, contributing to lipotoxicity, and insulin-resistant states may be linked to specific genetic variants. Case presentation This report presents a 27-year-old man with poor glycemic control, recurrent dizziness, extreme hypertriglyceridemia (TG > 37.87 mmol/L), insulin resistance, pancreatic fat infiltration, and early-stage diabetic nephropathy. Despite a family history of T2D, his clinical presentation far exceeded that of typical T2D. High-throughput sequencing revealed a heterozygous LRP6 variant (c.3107A>G, p.Asn1036Ser). Outcome Multidisciplinary treatment—incorporating acute-phase plasma exchange, ω-3 fatty acid ethyl ester 90, inclisiran, subcutaneous insulin aspart pump therapy, metformin, insulin icodec, finerenone, and Huangkui capsules—led to improvements in the patient’s metabolic indicators. Significance This case report describes a patient with type 2 diabetes mellitus presenting with extreme metabolic disorders, in whom a variant in the LRP6 gene was detected. Although the variant co-occurs with the observed phenotype, its pathogenicity cannot currently be established in the absence of functional validation. This case emphasizes that genetic variant screening should be considered in patients with unexplained severe metabolic disturbances, particularly those with early-onset disease. This case also provides a foundation for future functional studies and genetic confirmation.